Tafoni and Alveoles formation. An example from Naxos and Tinos Islands. - Evelpidou, N.; Leonidopoulou, D.; Vassilopoulos, A. (EU Natural Heritage from East to West, 2009)
Weathering formations resembling small caves, known by the name of Tafoni, are a characteristic, but not exclusive, feature of the Mediterranean area. Examples of such geomorphological formations have been recorded in Sardinia and Corsica (Klaer, 1956; Frenzel, 1965), in Tuscany (Martini, 1978), in S. Spain (Mellor et al., 1997) and in the Aegean Sea area (Greece) (Riedl, 1991; Hejl, 2005).